Difusão lexical em sintaxe (Revista de Estudos da Linguagem, 1992)
This paper discusses the possibility of the application ofthe Lexical Diffussion model to a syntactic phenomenon. It shows the importance oflexical parameters, Formality and Frequency, as factors of implementation of "Queísmo" and "Dequeísmo" in Portuguese. Statistical results demonstrate that the twoprocesses are only apparently opposite in the system and that they are, in fact, closely related, so that we can consider them as the sarne variatrion focus in thelanguage.